Delayed diagnosis of cryptococcal meningoencephalitis due to negative cryptococcal antigen test - Kessler, Bernhard (BMJ Publishing Group, 2013)
Cryptococcus spp. commonly causes infection in immunocompromised hosts. Clinical presentation of cryptococcal meningoencephalitis (CM) is variable, but headache, fever and a high intracranial pressure should suggest the diagnosis. The cryptococcal antigen test is a specific and sensitive rapid test that can be performed on blood or cerebrospinal fluid. We report a case of CM in a patient with previously undetected lymphocytopenia. Because cryptococcal antigen test results were negative, diagnosis and treatment were delayed.